The role of B-mode ultrasonography in the musculoskeletal anatomical evaluation of the cervical region of the dog spine - Sarto, Cibely G. [UNESP]; Hage, Maria Cristina F. N. S.; Guimarães, Luciana D.; Giglio, Robson F.; Borges, Andréa P. B.; Vulcano, Luiz Carlos [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2014)
This study characterized the normal musculoskeletal anatomy of the cervical segment of the spine of dogs by means of B-mode ultrasonography. The objective was to establish the role of B-mode ultrasonography for the anatomical evaluation of the cervical spine segment in dogs, by comparing the ultrasonographic findings with images by computed tomography and magnetic resonance imaging. The ultrasound examination, in transverse and median sagittal sections, allowed to identify a part of the epaxial cervical musculature, the bone surface of the cervical vertebrae and parts of the spinal cord through restricted areas with natural acoustic windows, such as between the atlanto-occipital joint, axis and atlas, and axis and the third cervical vertebra. The images, on transverse and sagittal planes, by low-field magnetic resonance imaging, were superior for the anatomical identification of the structures, due to higher contrast between the different tissues in this modality. Computed tomography showed superiority for bone detailing when compared with ultrasonography. As for magnetic resonance imaging, in addition to the muscles and cervical vertebrae, it is possible to identify the cerebrospinal fluid and differentiate between the nucleus pulposus and annulus fibrosus of the intervertebral discs. Although not the scope of this study, with knowledge of the ultrasonographic anatomy of this region, it is believed that some lesions can be identified, yet in a limited manner, when compared with the information obtained mainly with magnetic resonance imaging. The ultrasound examination presented lower morphology diagnostic value compared with the other modalities.

Este estudo caracterizou a anatomia musculoesquelética normal do segmento cervical da coluna vertebral de cães por meio da ultrassonografia modo B. O objetivo do trabalho foi estabelecer o papel da ultrassonografia modo B na avaliação anatômica do segmento cervical de cães, comparando os achados ultrassonográficos com imagens por tomografia computadorizada e ressonância magnética. O exame ultrassonográfico, em cortes transversais e sagitais mediano, permitiu a identificação de parte da musculatura epaxial do pescoço, superfície óssea das vértebras cervicais e medula espinhal em áreas restritas com janelas acústicas naturais, como entre a articulação atlantoccipital, áxis e atlas, e áxis e terceira vértebra cervical. As imagens, em planos transversais e sagitais, por ressonância magnética de baixo campo foram superiores na identificação anatômica das estruturas, devido ao maior contraste entre os diferentes tecidos nessa modalidade. A tomografia computadorizada se mostrou superior no detalhamento ósseo da região quando comparada ao exame ultrassonográfico. Já a ressonância magnética, além dos músculos e vértebras cervicais, permitiu a identificação do líquido cefalorraquidiano, e diferenciar núcleo pulposo e anel fibroso dos discos intervertebrais. Embora não seja objetivo direto deste estudo, com o conhecimento da anatomia ultrassonográfica dessa região, acredita-se que algumas lesões possam ser identificadas, contudo de maneira restrita, quando comparadas as informações obtidas, principalmente na imagem por ressonância magnética. O exame ultrassonográfico apresentou valor morfológico inferior.
O papel da ultrassonografia modo B na avaliação anatômica musculoesquelética do segmento cervical da coluna vertebral de cães
Keywords: Ultrassonografia musculoesquelética; segmento cervical; caninos; Musculoskeletal ultrasound; cervical segment; dogs